Refúgio no pinhal. Projecto de uma habitação de veraneio no pinhal de Ofir - Inês de Sousa Pereira Cubeles Lousan (2017)
The following dissertation approaches the construction of a summer house in the pinewood of Ofir, which offers to the ones who live it an intimate relationship with its surroundings, and also the proximity with the sea. The proposal arises from a will to return to a place, where a house already exists. This one, however, can no longer shelter all the members of the family that decided to build it, and besides that, it suffers from constant invasions due to the significant lack of protection on boundaries of the space, and fragility of the elements that should assure the safety of the building. The work process is presented in three parts. First, a contextualization and investigation about the initial construction in 1980, valuing the owner's opinion. Follows the evolution of the project which envolves: the contact with the client, the financing and development of a program, the formal definition and outdoor organizing, the design of interior spaces, and finally the search for a constructive solution that allows the simplification and systematization of the building process. In conclusion, a reflection is made, about the adopted method, and also a route, which presents the various moments lived since leaving the city until the presence in each space of the house.